Ecological characteristics of core-use areas used by Bering–Chukchi–Beaufort (BCB) bowhead whales, 2006–2012. (August 2015) - Citta, John J.; Quakenbush, Lori T.; Okkonen, Stephen R.; Druckenmiller, Matthew L.; Maslowski, Wieslaw; Clement-Kinney, Jaclyn; George, John C.; Brower, Harry; Small, Robert J.; Ashjian, Carin J.; Harwood, Lois A.; Heide-Jørgensen, Mads Peter
Highlights: We define core-use areas for Bering–Chukchi–Beaufort population bowhead whales. We summarize diving behavior, sea ice, and oceanographic data for each area. Core-use areas are co-located with oceanographic fronts and stratified layers. Seasonal movements relate to the timing of the ascent and descent of zooplankton. Whales feed seasonally in all three seas (Bering, Chukchi, and Beaufort). Abstract: The Bering–Chukchi–Beaufort (BCB) population of bowhead whales ( Balaena mysticetus ) ranges across the seasonally ice-covered waters of the Bering, Chukchi, and Beaufort seas. We used locations from 54 bowhead whales, obtained by satellite telemetry between 2006 and 2012, to define areas of concentrated use, termed "core-use areas". We identified six primary core-use areas and describe the timing of use and physical characteristics (oceanography, sea ice, and winds) associated with these areas. In spring, most whales migrated from wintering grounds in the Bering Sea to the Cape Bathurst polynya, Canada (Area 1), and spent the most time in the vicinity of the halocline at depths <75 m, which are within the euphotic zone, where calanoid copepods ascend following winter diapause. Peak use of the polynya occurred between 7 May and 5 July; whales generally left in July, when copepods are expected to descend to deeper depths. Between 12 July and 25 September, most tagged whales were located in shallow shelf waters adjacent to the Tuktoyaktuk Peninsula, Canada (Area 2), where wind-driven upwelling promotes the concentration of calanoid copepods. Between 22 August and 2 November, whales also congregated near Point Barrow, Alaska (Area 3), where east winds promote upwelling that moves zooplankton onto the Beaufort shelf, and subsequent relaxation of these winds promoted zooplankton aggregations. Between 27 October and 8 January, whales congregated along the northern shore of Chukotka, Russia (Area 4), where zooplankton likely concentrated along a coastal front between the southeastward-flowing Siberian Coastal Current and northward-flowing Bering Sea waters. The two remaining core-use areas occurred in the Bering Sea: Anadyr Strait (Area 5), where peak use occurred between 29 November and 20 April, and the Gulf of Anadyr (Area 6), where peak use occurred between 4 December and 1 April; both areas exhibited highly fractured sea ice. Whales near the Gulf of Anadyr spent almost half of their time at depths between 75 and 100 m, usually near the seafloor, where a subsurface front between cold Anadyr Water and warmer Bering Shelf Water presumably aggregates zooplankton. The amount of time whales spent near the seafloor in the Gulf of Anadyr, where copepods (in diapause) and, possibly, euphausiids are expected to aggregate provides strong evidence that bowhead whales are feeding in winter. The timing of bowhead spring migration corresponds with when zooplankton are expected to begin their spring ascent in April. The core-use areas we identified are also generally known from other studies to have high densities of whales and we are confident these areas represent the majority of important feeding areas during the study (2006–2012). Other feeding areas, that we did not detect, likely existed during the study and we expect core-use area boundaries to shift in response to changing hydrographic conditions.